STRATEGI DALAM PEMASARAN ONLINE GUNA MENINGKATKAN HASIL PENJUALAN - Eva Itma Anna (Jurnal Multimedia dan Android (JMA), 2022)
Abstract:Online marketing is an effort taken by companies to maintain their business amidst the popular use of social media ,which require people to stay at home and reduce outdoor activities. The object of this research is Sambal Seruit Bu Lin, a brand of instant sambal in Bandar Lampung city. The purpose of this qualitative study is to identify and analyze how online marketing strategy increase sales through Segmenting, Targeting, and Positioning (STP) and marketing mix suing case study. The focus of this research is obstacles encountered by the brand, the application of strategy, and sales development using online marketing. The primary data was obtained from interviews, and the secondary comes from documents, journal, etc., and SWOT analysis was conducted. This study finds that online marketing is effective to increase sales and that SWOT analysis is useful to highlights options of strategies to increase the sales.